Study On The Rock Quality Designation (RQD) And Groundwater Cavity Of The Kuala Lumpur Limestone Formation - Adzaman, Amir Faisal (Universiti Sains Malaysia, 2022)
Lithology is defined as rock and soil type (Kong, 2017). Geophysical, surface, and subsurface data are included in 3D geological models. The research was conducted in Kuala Lumpur, Malaysia and are divided into 3 cluster which area HKL, ESC and KBN. The objectives of this research were to study the Rock Quality Designation (RQD) of the limestone formation, to investigate potential groundwater cavity and to correlate the Rock Quality Designation (RQD) with the development of karst. The problem statement of this project are the presence of karst and the location of water inrush. The data received was in pdf format and converted it into excel format so that can be used into software. Then RQD value and lithology information are compared by using excel chart. Next, use the data given to create 3D modelling using visual KARSYS software and spatial distribution using Arcmap software. Finally, there were 16 boreholes with cavities that were only found in HKL and KBN. There are no cavity borehole in ESC cluster. It can be concluded that the higher the RQD value, the greater the likelihood of karst formation. Limestone forms karst in Malaysia's tropical and humid climate. As a result, lithology types can be influenced by the local weather. The research objectives were achieved. A cavity could cause the failure of a tunnel, road, or structure. Thus, prior to starting any project, learn about subsurface geology.